Hip range of motion is lower in professional soccer players with hip and groin symptoms or previous injuries, independent of cam deformities - Tak, I.; Glasgow, P.; Langhout, R.; Weir, A.; Kerkhoffs, G.; Agricola, R. (The American Journal of Sports Medicine, 2016)
Background: Soccer (football) players often have hip and groin symptoms (HGS), and a previous groin injury is a risk factor for a relapse. Decreased hip range of motion (HROM) has been related to both hip and groin pain and the presence of a cam deformity. How these factors interact is unknown.